Growing Washington's Prison Landscapes: A Design & Construction Guidebook - Golbuff, Graham (My University, 2016)
To date, no formal framework exists for utilizing a prison landscape as a means to reduce recidivism, improve facility safety, enhance operational and ecological functionality, and foster agency and empowerment in the lives of offenders and staff. Growing Washington’s Prison Landscapes represents an interdisciplinary attempt at defining, documenting and illustrating techniques to achieving those benefits through the activities of landscape design and construction. The resulting document contains standards and processes suitable for deployment at any prison facility in the state of Washington.
Thesis (Master's)--University of Washington, 2015-12
Keywords: Criminal Justice; Design / Build; Design Guidelines; Restorative Justice; Washington Department Of Corrections; Landscape architecture; landscape architecture